KONFLIK NINIK MAMAK DI KENAGARIAN KOTO TUO KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Reni Gusnita; M. Razif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research is motivated when M.Rasyid holds a Datuok Malintang , is where there is a conflict , each faction seized power among the descendants of Abdul Hadi Datuok Shoots ( Datuok Malintang ) with backrest Datuok Malintang Yahya camp . Though clearly Abdul Hadi who has been crowned the Datuok Malintang , while John was never crowned as Datuok Malintang and never too kua baewik , dagiong bacoca , while many witnesses still alive who saw when Abdul Hadi crowned Datuok Malintang . However ninik mamak Koto Tuo no longer much has changed in favor of the truth , no longer has the properties of a penghoeloe / ninik Mamak , no longer obey customary laws , similar to its already starvin+g wolf where there are many foods that they run and do not care background of children 's nephew , M. Rashid died in 2011 . before he died he had given a mandate to all prince / ninik mamak , that in writing , he reads mandate